Classification of Distinct Patterns of Ischemic Cholangiopathy Following DCD Liver Transplantation: Distinct Clinical Courses and Long-term Outcomes From a Multicenter Cohort. Issue 6 (30th August 2022) - Croome, Kristopher P.; Mathur, Amit K.; Aqel, Bashar; Yang, Liu; Taner, Timucin; Heimbach, Julie K.; Rosen, Charles B.; Paz-Fumagalli, Ricardo; Taner, C. Burcin
Abstract : Background: As the number of donation after circulatory death (DCD) liver transplants (LTs) performed in the United States continues to increase annually, there has been interest by policy makers to develop a more robust exception point safety net for patients who develop ischemic cholangiopathy (IC) following DCD LT. As such, there is a need for better understanding of the clinical course and long-term outcomes in patients who develop IC, as well as determining if IC can be classified into distinct categories with distinctly different clinical outcomes. Methods: All DCD LT performed at Mayo Clinic Florida, Mayo Clinic Arizona, and Mayo Clinic Rochester from January 1999 to March 2020 were included (N = 770). Outcomes were compared between 4 distinct radiologic patterns of IC: diffuse necrosis, multifocal progressive, confluence dominant, and minor form. Results: In total, 88 (11.4%) patients developed IC, of which 42 (5.5%) were listed for retransplantation of liver (ReLT). Patients with diffuse necrosis and multifocal progressive patterns suffered from frequent hospital admissions for cholangitis in the first year following DCD LT (median 3 and 2), were largely stent dependent (100% and 85.7%), and almost universally required ReLT. Patients with confluence dominant disease were managed with multiple stents and frequently recovered, ultimately becoming stent free without need for ReLT. Patients with the minor form IC did well with limited need for stent placement or repeat procedures and did not require ReLT. Graft survival was different between the 4 distinct IC patterns ( P  < 0.001). Conclusions: The present analysis provides a detailed analysis on the natural history and clinical course of IC. Patients developing IC can be classified into 4 distinct patterns with distinct clinical courses.